2015
DOI: 10.1080/08982112.2015.1037394
|View full text |Cite
|
Sign up to set email alerts
|

Bias Reduction of MLEs for Weibull Distributions under Grouped Lifetime Data

Abstract: Accelerated life tests (ALTs) usually contain subsampling because of the cost-effective evaluation. The two-stage method can deal with grouped data with subsampling, but the bias of maximum likelihood estimates (MLEs) can be alarmingly high. In this article, we propose reducing the bias of MLEs for grouped data via an unbiasing factor method. We introduce the procedures and give the unbiasing factor values. The proposed method is studied and compared with the modified maximum likelihood method for relative bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Table II shows that the values of log ηˆi obtained by the proposed method are larger than the results of Freeman and Vining's method, indicating that the maximum likelihood method underestimated log ηˆi. 15 The unbiased estimate of the shape parameter is βˆU = 2.7160, which is smaller than the Freeman and Vining's shape parameter estimate, βˆF V = 3.62. From Table II, we can see that there is a large difference between the c var log ηˆi ð Þ obtained by two methods.…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…Table II shows that the values of log ηˆi obtained by the proposed method are larger than the results of Freeman and Vining's method, indicating that the maximum likelihood method underestimated log ηˆi. 15 The unbiased estimate of the shape parameter is βˆU = 2.7160, which is smaller than the Freeman and Vining's shape parameter estimate, βˆF V = 3.62. From Table II, we can see that there is a large difference between the c var log ηˆi ð Þ obtained by two methods.…”
Section: Resultsmentioning
confidence: 69%
“…It can be easily proved that the ratio between the estimator and the shape parameter obtained from Yang and Lin is a pivotal quantity for complete and type II censoring, which can reduce the bias further via an unbiasing factor method. Accordingly, Wang et al . proposed reducing the biases of parameters through an unbiasing factor method; and their simulations showed that the unbiasing factor method developed is better than Yang and Lin's method for complete or censored data.…”
Section: Improved Two‐stage Approachmentioning
confidence: 99%
See 3 more Smart Citations